2023
DOI: 10.1007/s11469-023-01036-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Dimensions of the Parent–Child Relationship in Childhood as Longitudinal Predictors of Substance Use in Late Adolescence. The Mediating Role of Self-Control

Abstract: This study examined longitudinal links between several dimensions of parent–child relationship and adolescent substance use, and tested the role of self-control in mediating these. Data came from the Zurich Project on the Social Development from Childhood to Adulthood. Validated questionnaires were used to measure parent–child domains at age 11, self-control at age 13, and substance use at ages 13, 15, 17, and 20. Low positive parenting and parental supervision, as well as aversive parenting, correlated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Both attachment theory and empirical studies have demonstrated that close parent-child relationships could provide adolescents with a higher sense of emotional security and social support (Bowlby, 1982;Chiang & Bai, 2022), which benefits adolescents' self-development, social adjustment, and psychological well-being (Guan & Sun, 2018;Reitz et al, 2006). Conversely, poor parent-child relationships may put adolescents at risk for internalized problems, such as anger and depression, and externalizing problems, such as substance use, problematic mobile phone use, and peer victimization (Cheung et al, 2019;Qiu et al, 2022;Rodríguez-Ruiz et al, 2023;Zhou et al, 2023). As for the adolescents living in boarding schools, parental absence made them feel more alienated and threatened their perceived parent-child relationship (Barclay, 2011;, which in turn led to their emotional difficulties such as loneliness, loss of attachment, or homesickness (Schaverien, 2011) and negative behaviors such as smoking or fighting (Moswela, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both attachment theory and empirical studies have demonstrated that close parent-child relationships could provide adolescents with a higher sense of emotional security and social support (Bowlby, 1982;Chiang & Bai, 2022), which benefits adolescents' self-development, social adjustment, and psychological well-being (Guan & Sun, 2018;Reitz et al, 2006). Conversely, poor parent-child relationships may put adolescents at risk for internalized problems, such as anger and depression, and externalizing problems, such as substance use, problematic mobile phone use, and peer victimization (Cheung et al, 2019;Qiu et al, 2022;Rodríguez-Ruiz et al, 2023;Zhou et al, 2023). As for the adolescents living in boarding schools, parental absence made them feel more alienated and threatened their perceived parent-child relationship (Barclay, 2011;, which in turn led to their emotional difficulties such as loneliness, loss of attachment, or homesickness (Schaverien, 2011) and negative behaviors such as smoking or fighting (Moswela, 2006).…”
Section: Introductionmentioning
confidence: 99%